WILLIAM WALLACE AS A TRAGIC HERO PORTRAYED IN BRAVEHEART BY RANDALL WALLACE - , RANI FITRIYA WARDHANI; , Nur Saktiningrum, SS., M.Hum. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Braveheart is a novel that tells about the struggle of the people of Scotland to gain their freedom and independence. The main character in this novel is a protagonist named William Wallace, a commoner who become a leader of the Scottish army. At the end he dedicates his whole life for the country. This research attempts to find out what are the characteristics of William Wallace. Besides, it will also answer what William Wallaceâs motivation of fighting against the English and also how he can be characterized as a tragic hero. This graduating paper applied objective approach. This approach is chosen to analyze intrinsic elements such as plot, character, and characterization to reveal his tragic hero. Library research was applied in this graduating paper. The writer collected the data from the novel Braveheart written by Randall Wallace. The result of the study shows that William Wallaceâs characteristics are brave, persistent, and educated. However he also has a human weakness, his openness that makes him easily trapped by Craig and arrested by the English then he should die beheaded by an executioner. His motivations of fighting against the English are hope for rewards and revenge that send him into a great war and become a tragic hero as seen in the plot.